Investigation of a Large Diphtheria Outbreak and Cocirculation of Corynebacterium pseudodiphtheriticum Among Forcibly Displaced Myanmar Nationals, 2017–2019. (27th November 2020) - Weil, Lauren M; Williams, Margaret M; Shirin, Tahmina; Lawrence, Marlon; Habib, Zakir H; Aneke, Janessa S; Tondella, Maria L; Zaki, Quazi; Cassiday, Pamela K; Lonsway, David; Farrque, Mirza; Hossen, Tanvir; et al.
Abstract: Background: Diphtheria, a life-threatening respiratory disease, is caused mainly by toxin-producing strains of Corynebacterium diphtheriae, while nontoxigenic corynebacteria (eg, Corynebacterium pseudodiphtheriticum ) rarely causes diphtheria-like illness. Recently, global diphtheria outbreaks have resulted from breakdown of health care infrastructures, particularly in countries experiencing political conflict. This report summarizes a laboratory and epidemiological investigation of a diphtheria outbreak among forcibly displaced Myanmar nationals in Bangladesh. Methods: Specimens and clinical information were collected from patients presenting at diphtheria treatment centers. Swabs were tested for toxin gene ( tox )-bearing C. diphtheriae by real-time polymerase chain reaction (RT-PCR) and culture. The isolation of another Corynebacterium species prompted further laboratory investigation. Results: Among 382 patients, 153 (40%) tested tox positive for C. diphtheriae by RT-PCR; 31 (20%) PCR-positive swabs were culture confirmed. RT-PCR revealed 78% (298/382) of patients tested positive for C. pseudodiphtheriticum . Of patients positive for only C . diphtheriae, 63% (17/27) had severe disease compared to 55% (69/126) positive for both Corynebacterium species, and 38% (66/172) for only C. pseudodiphtheriticum. Conclusions: We report confirmation of a diphtheria outbreak and identification of a cocirculating Corynebacterium species. The high proportion of C. pseudodiphtheriticum codetection may explain why many suspected patients testing negative for C. diphtheriae presented with diphtheria-like symptoms. Abstract : We confirmed a large diphtheria outbreak among the forcibly displaced Myanmar nationals in Bangladesh and identified frequent cocirculation with azithromycin-resistant C. pseudodiphtheriticum among cases. Our investigation highlights the need to better understand the role of C. pseudodiphtheriticum as a pathogen.